Seismic processed data (Ocean Bottom Seismometer working area dataset) of RV SONNE during cruise SO297, Taltal Ridge, Chile - Arne Warwel; Dietrich Lange; Anke Dannowski; Heidrun Kopp (PANGAEA, 2025)
The data comprises processed active-source seismic data acquired with ocean bottom seismometer (OBS). The data were collected at the Taltal Ridge during expedition SO297 with the research vessel RV SONNE (doi:10.48433/cr_so297) offshore Taltal, north-central Chile (map for further details). The entire data set consists of 27 OBS stations. Seismic data were shot across the OBS along one profile. Each OBS consists of 4 channels (channel 1: hydrophone; channel 2: horizontal component 1; channel 3: horizontal component 2; channel 4: vertical component).